150 Jahre deutsche Verwaltungsgerichtsbarkeit - Hien, Eckart (De Gruyter, 2014)
The Baden Administrative Court was the first administrative court to be established in Germany and began its work in October 1863 in Karlsruhe. In 2013, the anniversary of its founding provided the occasion to reflect on the 150-years history of administrative justice in Germany. The essay is based on a lecture delivered by the then President of the Federal Administrative Court to mark the anniversary.
Keywords: Appellate courts -- Germany.; LAW -- Essays.; LAW -- General Practice.; LAW -- Jurisprudence.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; LAW -- Reference.; Appellate courts.; Germany.; Electronic books.